2021
DOI: 10.1136/bmjopen-2021-052886
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the timely initiation of antenatal care: findings from a cross-sectional study in Northern Bangladesh

Abstract: ObjectiveThis paper explored the factors that influence the timely initiation of antenatal care (ANC) in Bangladesh.DesignThis was a cross-sectional survey.SettingThis study conducted in two rural subdistricts and one urban area from three Northern districts of Bangladesh from August to November 2016.ParticipantsWomen who had a live birth in the last 1 year prior to data collection were enrolled for this study. In each study area, around 900 women were interviewed, and finally, we completed 2731 interviews.Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 51 publications
4
11
2
Order By: Relevance
“…Women with higher levels of education are more likely to have optimal timing for ANC initiation and optimal ANC visits. This nding is consistent with previous research [13,17,20,22,53]. This is because education improves health-care utilization and increases knowledge about speci c issues.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Women with higher levels of education are more likely to have optimal timing for ANC initiation and optimal ANC visits. This nding is consistent with previous research [13,17,20,22,53]. This is because education improves health-care utilization and increases knowledge about speci c issues.…”
Section: Discussionsupporting
confidence: 92%
“…The independent variables that are potentially affected by optimal ANC visits and timing of ANC initiation were maternal age group, region, place of residence, mother's education level, religion, family size, sex of household head, wealth index, total children ever born, marital status, and place of delivery. The independent variable was taken from previous studies that are published worldwide [9,[12][13][14][15][16][17][18][19][20][21][22].…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a recent multi-country analysis of Demographic and Health Surveys from sub-Saharan Africa, it was found that the percentage of pregnant women commencing timely ANC visits ranged from 14.5% in Mozambique to 68.6% in Liberia. 24 Findings from several other LMICs reported that the prevalence of initiating timely ANC attendance was as low as 11% in a geographic region of Bangladesh, 36 and as high as 65.7% in an urban area in Ethiopia. 20 In Ethiopia, three studies from three regions of the country reported early ANC initiation of 19.5%, 37 31.5%, 17 and 57.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from LMICs reported significant associations between timely initiation of ANC attendance by pregnant women and women’s age, 17 , 18 , 20 , 22–25 , 30–32 , 37 wealth status, 18 , 24 , 25 , 31 , 33 , 37 education, 18 , 21–25 , 29 , 31 parity, 18 , 20 , 23–27 , 29 , 32 access to media, 23 , 24 , 28 , 31 , 38 pregnancy intention, 16 , 19 , 21 , 23 , 24 , 26 , 27 , 29–31 , 39 residential area, 24 , 29 , 36 family size, 17 , 29 and husband’s education. 19 , 36 Except for the statistically insignificant correlation of husband’s education with pregnant women’s timely ANC attendance, our findings on the higher odds of pregnant woman’s timely ANC attendance by age, education, wealth status, parity, pregnancy intention, residential area, and access to media were fairly consistent with previous studies. A recent study, which used data from the demographic and health survey (DHS) of 36 African countries, found strong associations of sociodemographic and contextual factors with the likelihood of timely initiation of ANC visits by pregnant women.…”
Section: Discussionmentioning
confidence: 99%